Finally Time for Realistic and Determinate Standards in Family Court. (March 2017) - Gupta‐Kagan, Josh
Abstract: The child protection field has long recognized that legal standards applied by family courts are both broad and vague—definitions of abuse and neglect encompass a wide range of behavior, and substantive standards governing disposition hearings, foster care placements, and permanency hearings provide little guidance. This status quo empowers child protection agencies—who can take advantage of broad and vague standards to obtain judicial approval when they want to intervene. As a result, judicial checks and balances are weaker and reform efforts are more agency‐dependent than they ought to be. The weak legal and judicial checks enable the child protection pendulum to swing widely. Narrower and more precise legal standards can mitigate those problems. They can also improve current reform efforts by providing clearer standards for when court intervention is appropriate, and thus help distinguish cases which need court intervention from those that do not—a central challenge of existing reform efforts. This Article outlines several principles for stronger legal standards. First, standards should balance future risk, with adequate weight given both to risks of future child maltreatment and to risks of harms imposed by the court or foster care systems. Second, standards should apply lessons from social science research—and should evolve in light of future research. Third, they should follow a firm evidentiary record in the case. These principles should shape standards for all essential decisions, not only those that are typically litigated at a trial. Whether a child is removed, what conditions are required for reunification, and where and with whom a child lives while in foster care, for instance, can all be the most important questions in any given case, and deserve clearer legal guidance. This Article will apply these principles to several such decisions. Finally, this Article will identify two systemic features necessary to make standards more effective—vigorous advocacy for all parties, and access to appellate courts to decide interlocutory—but often decisive—issues.